(untitled) (Research, Society and Development, 2022)
COVID-19 pandemic has affected higher education around the world. Specially in dentistry courses that paralyzed their practices and, currently, returned to their activities with several biosafety adjustments to ensure a safe return. This work aimed to contribute with the discussion of the impacts of the pandemic on Brazilian dental education in these two years. A two-year exploratory and comparative narrative review and document analysis were carried out. There was an initial free search for official documents and technical notes. Afterwards, search for scientific articles in the Web of Science, PubMed, EBSCOhost and GoogleScholar databases with the descriptors: COVID-19 AND dentistry AND guidelines AND dental education ou COVID-19 AND odontologia AND diretrizes AND ensino odontológico. Then, data were organized in spreadsheets and compared. Adaptations were proposed in the forms of embracing, reception and patient care, in order to avoid contamination in collective environments. Social distance, teleassessment, correct behavior towards symptomatic patients, as well as the use of new personal protective equipment also were implemented. Some existing measures such as hand hygiene were reinforced, as is one of the main forms of prevention against SARS-CoV-2 and other pathogens. It was verified the necessity to assure to the users adequate ventilation of the environment to avoid the spread of aerosols generated during care. In front of this scenario that drives transformations In dental education and considering the possibility of new pandemics, it is essential to include training and protocols for crisis management during health meltdowns in dental education.